Pengolahan Air Terproduksi Berbasis Teknologi Hybrid Sebagai Upaya Mitigasi Risiko Bahaya Lingkungan dan K3 di PT XYZ - Santoso, Teguh; Cahyono, Rochim Bakti (Universitas Hang Tuah Pekanbaru, 2025)
Produced water is the main waste generated from oil and gas exploration and production activities, containing hazardous organic and inorganic compounds such as phenol, ammonia, sulfide, as well as oil and grease, which have the potential to pollute the environment and pose risks to occupational health and safety (OHS), particularly from exposure to H₂S and ammonia gases. This study employed an experimental design through laboratory testing and pilot-plant simulation, comprising aeration, coagulation–flocculation, biological aeration, and filtration processes at the wastewater treatment plant (WWTP) of PT XYZ in Indramayu. Samples were collected from the WWTP inlet and outlet using the composite sampling method over a four-month period (April–August 2025), totaling 153 samples with triplicate tests for each parameter, including temperature, pH, oil and grease, COD, phenol, sulfide, and ammonia, in accordance with APHA (2017) standards. The results showed that the hybrid system reduced oil and grease, COD, phenol, and ammonia by more than 80%, and sulfide by more than 70%, indicating that the effluent met the quality standards set by the Ministry of Environment Regulation No. 19 of 2010. The application of hybrid technology proved to be technically effective, operationally safe, and contributed to mitigating OHS risks and supporting environmental sustainability in the upstream oil and gas industry. Further research is recommended to focus on a more detailed analysis of additional parameters such as heavy metals (Hg, Pb, Cd) and organic micro-pollutants to obtain a more comprehensive understanding of the system’s effectiveness and potential environmental impacts.